Pola Materi Kebahasaan, Monitoring, dan Evaluasi Pembelajaran Bahasa pada Buku Tematik Sekolah Dasar Kelas 1 - Yenny Puspitawati; Markhamah Markhamah (Jurnal Penelitian Humaniora, 2021)
This research has two aims. 1) to describe the pattern of lan-guage learning in primary school thematic text-books used in grade 1; and 2) to describe how to monitor and evaluate lan-guage learning in school thematic text-books used in the basic class in grade 1. By using the method of listening and tapping as well as note-taking techniques, we collected our data sourced from the 2013 thematic integrated curriculum book for elementary school students grade one. The data that have been obtained are then analyzed and presented formally in the narrative form. The results of this study indicate that of the 8 themes that are represented in the 8 books are able to pre-sent aspects and language competencies that are rather sys-tematic. In addition, the training and evaluation monitoring sheet in the form of "Now I Can" can make it easier for teach-ers to measure the achievement and success of each student's learning comprehensively and validly.